350PLow-dose cisplatin and 5-fluorouracil combined concurrent chemoradiotherapy for unresectable cutaneous squamous cell carcinoma: Analysis of 23 cases. (24th November 2019) - Hiura, A; Yoshino, K; Maeda, T; Oaku, S; Nagai, K; Kato, M; Yamashita, C; Uehara, J; Fujisawa, Y
Abstract: Background: Currently, various chemotherapy regimens have been reported for the efficacy of unresectable squamous cell carcinoma (cSCC). However, there is no clear consensus. Here, we report the treatment results of unresectable cSCC in which concurrent chemoradiotherapy (CCRT) combining low-dose cisplatin and 5-fluorouracil (low-dose FP therapy) was performed in our department. Methods: A two-year retrospective study was conducted for 23 patients who had been received CCRT with low-dose FP therapy for unresectable cSCC. The patient age ranged from 44 to 79 years (mean age, 71 years), and gender was 17 men and 6 women. The primary lesions of unresectable cSCC were present in 7 cases in the head and neck, in 1 case in the upper limbs, in 5 cases in the lower limbs, and in 10 cases in the perineal region. Radiotherapy (RT) of CCRT had irradiated the primary lesion and regional lymph nodes. And for chemotherapy of CCRT, low-dose FP therapy was used. Results: When 23 patients were classified by TNM staging (UICC 8th), stage 3 of unresectable cSCC was 5 patients (21.7%) and stage 4 was 18 patients (78.3%). 6 cases who those with stage 4 were dead (26.1%), while there were no dead cases who those with stage 3. Overall response rate (ORR) was 81 %, and median progression-free survival (PFS) was 392 days. For stage 4 of unresectable cSCC, one-year overall survival (OS) was 78 %, two-year OS was 56.7%, median survival time (MST) was 560 days. Conclusions: CCRT with low-dose FP therapy is an effective treatment for unresectable cSCC. However, tumors of the primary lesion and / or regional lymph nodes may remain after CCRT. In such cases, chemotherapy (i.e., maintenance therapy [MT]) should be continued after CCRT. In our department, most cases of unresectable cSCC receive MT after CCRT. Therefore, in the first treatment of unresectable cSCC, it is important how to make the tumor smaller. In this study, our cases had optimal results of ORR, median PFS, OS, and MST. According to these facts and results, we considered CCRT with low-dose FP therapy suppressed cSCC and is an effective treatment. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.